ANALISIS PENINGKATAN KEPUASAN PELANGGAN PADA RESTORAN BALE RASA PONOROGO - Santoso, Adi; Ananda, Yudha Rizky (STIE Muhammadiyah Tanjung Redeb, 2019)
This research is about an analysis of increasing customer satisfaction in Bale Rasa Restaurant in Ponorogo. The purpose of conducting this research is the first to find out how the effect of service quality on customer satisfaction, second to find out the influence of interior displays on customer satisfaction and the third to determine the effect of store layouts on customer satisfaction. The object of this study is Bale Rasa restaurant customers in Ponorogo. This research is quantitative research and survey. The population of this study was the customers of Resto Bale Rasa and the samples used in this study amounted to 100 customers selected using the random sampling method. The method of data collection is done by using questionnaires and documentation. The results of this study partially found that service quality variables and store layouts had a positive and significant effect on the customer satisfaction level of Bale Rasa Resto while the interior display variable was found to have no significant effect on increasing customer satisfaction Resto Bale Rasa.